Exotic Citrus Diseases: Early Detection is the Solution to Protecting Florida Citrus - Jamie D. Yates; Megan M. Dewdney; Ronald H. Brlansky (EDIS)
CH202, a 2-page illustrated trifold brochure by J.D. Yates, M.M. Dewdney, and R.H. Brlansky, is best viewed in PDF format. It provides key information about citrus blackspot, sweet orange scab, citrus leprosis virus, citrus variegated chlorosis (CVC), and citrus tristeza virus (CTV) stem pitting. Includes contact information for UF/IFAS Extension citrus experts. Published by the UF Department of Plant Pathology, November 2008.